An improved PCR-mutagenesis strategy for two-site mutagenesis or sequence swapping between related genes. - Kirsch, R D (1998)
The QuikChangeTM protocol is one of the simplest and fastest methods for site-directed mutagenesis, but introduces mutations at only one site at a time, and requires two HPLC-purified complementary oligonucleotides. Here, we describe that this method can be used with non-overlapping oligonucleotides. By doing this, two separate sites can be mutagenised simultaneously, or money can be saved by using a second 'standard' oligonucleotide. By a further modification, we have also used the QuikChangeTM approach to exchange DNA sequences between closely related genes.